Do Mitochondrial Replacement Techniques Affect Qualitative or Numerical Identity?. (14th December 2016) - Liao, S. Matthew
Abstract: Mitochondrial replacement techniques (MRTs), known in the popular media as 'three‐parent' or 'three‐person' IVFs, have the potential to enable women with mitochondrial diseases to have children who are genetically related to them but without such diseases. In the debate regarding whether MRTs should be made available, an issue that has garnered considerable attention is whether MRTs affect the characteristics of an existing individual or whether they result in the creation of a new individual, given that MRTs involve the genetic manipulation of the germline. In other words, do MRTs affect the qualitative identity or the numerical identity of the resulting child? For instance, a group of panelists on behalf of the UK Human Fertilisation and Embryology Authority (HFEA) has claimed that MRTs affect only the qualitative identity of the resulting child, while the Working Group of the Nuffield Council on Bioethics (NCOB) has argued that MRTs would create a numerically distinct individual. In this article, I shall argue that MRTs do create a new and numerically distinct individual. Since my explanation is different from the NCOB's explanation, I shall also offer reasons why my explanation is preferable to the NCOB's explanation.